2022
DOI: 10.1097/mou.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytoreductive surgery in the era of immunotherapy

Abstract: Purpose of reviewThe benefit of cytoreductive nephrectomy (CN) in metastatic renal cell carcinoma (mRCC) was first called into question in the tyrosine kinase inhibitors (TKIs) era. It remains undefined in the context of the recent development and approval of immune checkpoint inhibitors (ICIs) and level one evidence supporting the rapid adoption of dual ICI and combination ICI þ TKI therapeutic approaches for mRCC. Our objective is to synthesize the available contemporary data regarding the safety, feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…Роль циторедуктивных операций при современном арсенале системной терапии для пациентов с мПКР четко не определена [7]. При решении вопроса о целесообразности ЦНЭ при мПКР решающую роль играют отбор пациентов, группа прогноза по IMDC, что особенно важно при медленно растущих метастазах, когда можно длительно наблюдать пациента до прогрессирования [4].…”
Section: Discussionunclassified
“…Роль циторедуктивных операций при современном арсенале системной терапии для пациентов с мПКР четко не определена [7]. При решении вопроса о целесообразности ЦНЭ при мПКР решающую роль играют отбор пациентов, группа прогноза по IMDC, что особенно важно при медленно растущих метастазах, когда можно длительно наблюдать пациента до прогрессирования [4].…”
Section: Discussionunclassified
“…Pignot et al concluded that delayed CN in patients who responded to ICI treatment provided promising oncological outcomes, and most patients could discontinue systemic treatment ( 20 ). However, from a surgical perspective, ICI-based combination therapy results in a severe desmoplastic reaction, which increases perinephric adhesions and inflammation, thus increasing surgical complexity ( 21 ). Accordingly, ongoing prospective studies, such as PROBE and NORDIC-SUN, will better define the role of CN in the rapidly evolving treatment landscape of mRCC in combination with ICI-based systemic therapy.…”
Section: Discussionmentioning
confidence: 99%